PENATALAKSANAAN FISIOTERAPI PADA PASIEN PENDERITA PNEUMONIA DAN CHRONIC OBSTRUCTIVE PULMONARY DISEASE : STUDI KASUS - Riyanto, Azmi Fitrah Mithra; Widodo, Agus; Utami, Multasih Nita (Prosiding University Research Colloquium, 2024)
Case presentation: Bp. TH, aged 73, is known to have suffered from pneumonia due to a bacterial infection of Streptococcus pneumonia in the lower respiratory tract. In addition, the patient has suffered from chronic obstructive pulmonary disease (COPD) and cardiomegaly, the patient is a smoker. The patient suffered from shortness of breath accompanied by coughing and chest pain on Monday, October 30, 2023. The patient was transferred to RSUD Paru Dungus for treatment. Methods: This study is a kind of case report or case study. The Modified Medical Research Council (mMRC) dyspnea scale is used to measure the degree of dysplasia during activity due to shortness of breath. To measure the degree of difficulty for the patient to breathe using a modified borg scale rate of perceived exertion. Thorax cage development is measured using the midline, and oxygen saturation (SPO2) measurement is done using a fingertip pulse oximeter. Results: systolic blood pressure drops from 160 mm Hg to 130 mm Hg. SPO2 increases by 4%. The Borg scale decreases from 4 (sort of hard) to 2. (easy). Conclusion: There is an increase in SPO2 oxygen saturation levels, and shortness of breath complaints have decreased on the measurement results of the mBorg scale, but measuring the mMRC dyspnea scale shows no change either, which can be understood to mean that there has been no improvement or decrease in disability when performing activity due to shortness. Keywords: Pneumonia; COPD; Dyspnea PENATALAKSANAAN FISIOTERAPI PADA PASIEN CHRONIC OBSTRUCTIVE PULMONARY DISEASE DENGAN KOMORBID PNEUMONIA: STUDI KASUS AbstrakPresentasi kasus: Bp. TH, usia 73 tahun diketahui menderita pneumonia akibat infeksi bakteri streptococcus pneumoniae pada sistem saluran napas bawah. Selain itu pasien di diagnosa telah menderita chronic obstructive pulmonary disease (COPD) , cardiomegaly dan pasien adalah perokok. Pasien mengalami sesak nafas disertai dengan batuk dan nyeri dada pada hari senin 30-10-2023, pasien dilarikan ke RSUD Paru Dungus untuk dirawat. Metode: Studi ini berjenis case report atau studi kasus. Modified medical research council (mMRC) dyspnea scale digunakan untuk mengukur tingkat disablitas pada saat melakukan aktifitas akibat sesak napas. Untuk mengukur tingkat kesulitan pasien untuk bernapas menggunakan modified borg scale rate of perceived exertion. Pengembangan sangkar thorax diukur menggunakan midline dan pengukuran saturasi oksigen (SPO2) menggunakan fingertip pulse oximeter. Hasil: Tekanan darah sistol menurun dari 160 mm Hg menjadi 130 mm Hg. Peningkatan SPO2 sebanyak 4%. Penurunan nilai skala borg dari skor 4 (sort of hard) menjadi 2 (easy). Kesimpulan: Adanya peningkatan kadar saturasi oksigen SPO2 ,keluhan sesak napas mengalami penurunan pada hasil pengukuran mBorg scale akan tetapi untuk pengukuran mMRC dyspnea scale tidak menunjukkan perubahan maupun, yang dapat diartikan bahwa belum ada perbaikan atau penurunan disabilitas ketika melakukan aktifitas akibat sesak napas.